2002
DOI: 10.1073/pnas.142284899
|View full text |Cite
|
Sign up to set email alerts
|

Restricted islet-cell reactive T cell repertoire of early pancreatic islet infiltrates in NOD mice

Abstract: The mechanisms responsible for initiating autoimmune diabetes remain obscure. Here, we describe a method for identifying both the ␣-and ␤-chains of the T cell receptor (TCR) from individual pancreatic islet-infiltrating T cells at the earliest stages of disease in nonobese diabetic mice (NOD). Analysis of the TCR repertoire of these early islet infiltrates reveals enrichment for a small subset of TCR sequences. Reconstitution of these TCR in vitro demonstrates that these receptors confer reactivity to islet ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
78
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 65 publications
9
78
0
Order By: Relevance
“…In contrast with established primer sets for the amplification of TCR CDR3 regions from single T cells (10,13,14,45), our primers amplify full-length variable regions. In the elegant study by Ozawa and colleagues (9), they were able to generate matching TCR a/b cDNAs from approximately 20% of processed single cells using the 5 0 -RACE technique.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with established primer sets for the amplification of TCR CDR3 regions from single T cells (10,13,14,45), our primers amplify full-length variable regions. In the elegant study by Ozawa and colleagues (9), they were able to generate matching TCR a/b cDNAs from approximately 20% of processed single cells using the 5 0 -RACE technique.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of Asp57 not only gives the potential to interact with peptides containing acidic residues at P9 but also with T-cell receptors with a negatively charged CDR3b loop. 36 The relationship between DR8 and these alleles was further confirmed by analyzing the theoretical capacity of DR8 peptides to binding DQ8, I-A g7 and DQ2, using the MHC2Pred tool for prediction of promiscuous MHC class II binders (http://www.imtech.res.in/raghava/ mhc2pred/). Of the 216 DR8 sequences analyzed, 59 and 51%, respectively, were potential good binders to DQ8 and I-Ag7, using a very stringent threshold of 1.…”
Section: Hla-dr8-binding Motif L Muixí Et Almentioning
confidence: 97%
“…1A shows a dot plot of pancreatic lymphocytes from a 9-wk-old NOD mouse in which B cells (B220 ϩ ) and T cells (CD3 ϩ ) are found in roughly even proportions (7.9 and 8.7%, respectively, B:T ratio, 0.48). The unstained population in this assay is due to pancreatic tissue components, including islets that segregate with lymphocytes in density, size, and granularity (24). To evaluate the possible contribution of non-isletinvading lymphocytes, such as those from blood vessels in the pancreas, we used nonautoimmune C57BL/6 mice, in which there is no insulitis, as controls.…”
Section: Lymphocytes In the Islets Of Prediabetic Nod Mice Form Tertimentioning
confidence: 99%
“…In particular, little is known about B lymphocytes within these foci of autoreactivity. Studies on T cell receptors have shown oligoclonality within isolated islets, with a polyclonal repertoire across the pancreas as a whole (23,24), but their relationship to regional lymph nodes was not explored. Studies of cellular dynamics revealed that B and T lymphocytes invade the islets concurrently (25) and that CD4 ϩ T cell priming and proliferation occur in draining pancreatic lymph nodes before the onset of insulitis (26 -28), suggesting a collaborative relationship between these secondary lymphoid organs and TLS in the islets.…”
mentioning
confidence: 99%